Preparing a scale for sports knowledge management and standardizing it for employees in student activities departments in Iraqi universities - Shakir Mahmoud Abdullah; Zeyad Mishaal Farhan; Yaseen Ali Khalaf; Omar Fadhil Yahya; Othman Adham Ali (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The importance of the research lies in the need to exchange sports knowledge between principals and their assistants and all workers in the field of extracurricular student activities, especially in the sports field.